Doczekać się bezimienności. Broniewski chórem lub na głosy - Tramer, Maciej (Śląskie Studia Polonistyczne, 2020)
The article To live to see namelessness. Broniewski chorally or for part-singing is devoted to the project by the Gallery Raster entitled Broniewski. The event took place in Warsaw in November and December 2005. The organizers of the exhibition succeeded in persuading artists connected with independent art and stage to participate in the project. Although the project of the Gallery Raster is entitled and described using the name of only one poet, the event had a communal character. According to the author of the article To live to see namelessness…, this character is one of the main determinants of Władysław Broniewski as a person and of the phenomenon of his poetry.